A simple amplitude detector-based demodulator for resolver converters - Kaewpoonsuk, Anucha; Katman, Ratchanoo; Kamsri, Thawatchai; Rerkratn, Apinai; Riewruja, Vanchai (My University, 2010)
This paper presents a simple method based on sinusoidal-amplitude detector for realizing the resolver-signal demodulator. The proposed demodulator consists of two full-wave rectifiers, two ±unity-gain amplifiers, and two sinusoidal-amplitude detectors with control switches. Two output voltages are proportional to sine and cosine envelopes of resolver-shaft angle without low-pass filter. Experimental results demonstrating characteristic of the proposed circuit are included. ©ICROS.
Keywords: Amplitude detector; Demodulator; Resolver converter